Examining the impact of visual presentations and online reviews on hotel booking intentions - Amin, Dawood (SAGE Publications, 2021)
This study aims to examine the factors affecting the behavioural intentions toward online hotel booking. The study integrates visual presentations and online reviews with the technology acceptance model (TAM). Partial least squares structural equation modelling (PLS-SEM) was used to test the proposed hypotheses in this research. The results report that booking intentions are mainly determined by visual presentations and perceived usefulness. The statistical analysis supports the notion that visual presentations and online reviews have a positive impact on perceived usefulness and perceived ease of use. However, online reviews do not have any significant influence on booking intention directly. The study concludes that online consumers are more likely to book a hotel online if visual presentations and online reviews appear to be useful and easy to use. The findings contribute several implications for researchers and practitioners in the hospitality field.